An unusual and rare presentation of mature cystic teratoma in a post menopausal woman - Quraishi, Abdul H.; Jena, Sanjib K.; Umare, Girish; Borkar, Sushrut (International Surgery Journal, 2022)
It is rare to encounter benign forms of mature cystic teratoma in elderly women. It has been reported that the risk of malignant transformation is doubled in patients with mature cystic teratoma aged over 50 years. We reported a case of a 52-year-old woman with a large pelvic mass. The imaging and operative findings have been described. The diagnosis was confirmed on histopathology as mature cystic teratoma.